Kontribusi Sosial Mahasiswa Pmm 3 Inbound Unkhair Dalam Upaya Peningkatan Kesadaran Lingkungan Masyarakat Sekitar Pantai Marimbati Dan Objek Wisata Gamtala - Br Napitupulu, Dameria Sofyana; A.L. Tobing, Chatrine Sopia; Ginting, Juandro Prananta; Indah Arum, Fina Yuli Asri (Journal Of Human And Education (JAHE), 2024)
Social Contribution is one of the Independent Student Exchange (PMM) activities. Social contribution activities were carried out in December at the tourist destination Gamtala and Marimbati beach, Jailolo, West Halmahera. This social contribution activity is carried out by involving PMM students and the surrounding community to maintain cleanliness and increase environmental awareness in the community around the tourist area. This social contribution activity is part of the archipelago module activities. which focuses on real action in one of the Indonesian cultures, the characteristics of family and mutual cooperation. This method of implementing social contributions plays a role in maintaining cleanliness and increasing understanding of environmental awareness in the Gamtala and Marimbati Beach tourist attraction areas. The results of this social contribution make the area around the Gamtala tourist attraction and Marimbati beach more beautiful and clean. This writing aims to provide students with experience to make a real contribution in maintaining environmental cleanliness at tourist attractions and increase public awareness of the importance of environmental cleanliness. Keywords: Social Contribution, Archipelago Module, Environmental Awareness. Cleanliness, Trash.